Analysis of Companies’ Restructuring Goals - Bivainis, Juozas; Tamošiūnas, Andrius (Ekonomika, 2003)
Restructuring is one of the essential ways of strategic management solving problems of companies’ business extension and efficiency increase under the clearly defined time perspective. Typically, a wide spectrum of set of measures and methods is applied and sought to implement at least a several goals when restructuring a company. Analysis of goals of restructuring companies in European Union and US shows, that business macroeconomic environment is one of most significant factors determining the company’s restructuring goals. Restructuring companies in the countries of these different continents (EU and US), the following goals were distinguished as the dominating ones: to reduce excess of the capacity (US – 37%), to extend the market (EU – 32.4%, US – 36%), to maintain the current market positions (EU – 44.4%). The regularities characteristic to the structure of goals of companies’ restructuring in the explored four economy sectors of Lithuania are following: for the sector of financial service – increase of liquidity of assets (especially when restructuring state banks in the period of 2001–2002), implementation of new products, market extension; for the insurance services – market extension, maintenance of market position, implementation of new products; for the energy resources – increase of liquidity of assets (often implementing modem technologies), reduction of debts of residents and municipalities (especially for district heating companies), management improvement; for the beer industry – market extension, implementation of new products (especially in the period of 1997–2000), increase of liquidity of assets. Looking to the explored Lithuanian financial, insurance services, energy resources sectors and the beer industry as to a whole complex, the dominating goals of companies’ restructuring in 1998–2002 were the following: increase of liquidity of assets (26%), market extension (21%), implementation of new products (20%). Lithuanian companies’ restructuring, from the point of view of the goals structure, becomes alike to those of countries with efficiently functioning market. This is one of outcomes of Lithuanian economy integration to EU and other economic structures of world. Determined regularities of companies’ restructuring goals in Lithuania and other countries as well as tendencies of revealed the goals’ structure may be useful for business of Lithuania when taking over the great experience of companies restructuring in other countries.